ANALISIS PERSELISIHAN ANTARA ORGANISASI KARANG TARUNA DAN ORGANISASI CIGARKAS DI LINGKUNGAN KP. CIPTAKARYA - Ageng Saepudi Kanda; Bunga Nurmaulidina (JURNAL ILMIAH RESEARCH STUDENT, 2024)
In rural and urban communities, youth organizations or sinoman play a very important role in advancing physical and non-physical development because the young generation is the future leader. So that conflicts occur between youth organizations which result in delays in achieving the vision and mission of a community or village environment. Therefore, this research aims to explain the influence of attitudes between youth organizations in the community environment in KP. Ciptakarya by means of youth empowerment is a process of increasing the abilities and strengths of youth, so that by empowering youth they are able to realize their potential, are able to use this potential to fulfill their daily needs, and are able to participate in various social activities and development processes. Youth empowerment is a process utilize and develop the potential of young people to strengthen their abilities so that later they can achieve independence.